Analysis of Multi-Mycotoxins in Commonly Consumed Spices Using the LC-MS/MS Method for Assessing Food Safety Risks - Burak Demirhan; Buket Er Demirhan (Microorganisms, 2023)
Mycotoxins are secondary metabolites produced by certain fungal species. In this study, the aim was to investigate mycotoxins, which pose a serious health problem. For this purpose, a total of 140 spice samples (black pepper, red pepper, cumin, and turmeric) purchased from Ankara, Turkey, were analyzed for specific mycotoxins (aflatoxin B1-AFB1, aflatoxin B2-AFB2, aflatoxin G1-AFG1, aflatoxin G2-AFG2, ochratoxin A-OTA, zearalenone-ZEN) using an LC-MS/MS multi-mycotoxin method. The Staphylococcus spp. and Micrococcus spp. counts in the spice samples were also analyzed using the conventional culture method. The contamination levels of AFB1 ranged from not detected (ND) to 39.12 μg/kg; AFB2 ranged from ND to 2.10 μg/kg; AFG1 ranged from ND to 0.92 μg/kg; AFG2 ranged from ND to 3.67 μg/kg; OTA ranged from ND to 39.79 μg/kg; ZEN ranged from ND to 11.16 μg/kg. The maximum residue limit for AFB1 (5 μg/kg) determined according to the Turkish Food Codex (TFC) was exceeded in five samples of red pepper, two samples of black pepper, and one sample of turmeric. Furthermore, it was determined that three samples of red pepper and one sample of black pepper exceeded the maximum limits for total aflatoxin (10 μg/kg) and OTA (15 μg/kg) specified in the TFC.